(untitled) (Research, Society and Development, 2020)
This study aimed to evaluate how medical emergencies attended by the First Aid Service Post - PAPS, quantifying as clinical occurrences of dental interest. It is a documentary, descriptive and transversal research with a quantitative approach. To do this, perform an evaluation of the medical records of the First Aid Service Post - PAPS with the collection of information that meets the objectives of the study. The data were recorded on a registration form for further analysis. The universe consisted of 6,000 records and a sample selected by 501 records in 2015. Clinical occurrences correspond to 21% of the survey. As for the most common occurrence, lipothymia was the most frequent (36%) and the highest prevalence was female with 73%. The highest number of occurrences was carried out in young people, between 16 and 30 years old, corresponding to 77% and SAMU was activated in 15% of the occurrences. It is up to the professionals to carry out a well-performed anamnesis before the care, minimizing as possible complications that may occur before, during or after the care, after that, the dentists must be able to intervene properly.